KKN INTERNASIONAL STIT INTERNASIONAL MUHAMMADIYAH BATAM: METODE PENGAJARAN KETERAMPILAN BAHASA ARAB BAGI SANTRI DARUL HUFFAH JOHOR, MALAYSIA - Fatiah; M. Nurman Ardiansyah (LPPM STAI Muhammadiyah Probolinggo, 2025)
The teaching of Arabic in international Islamic boarding schools, such as Madrasah Darul Huffah Johor, still faces significant challenges in improving students’ productive language skills, particularly in speaking and writing. This is due to the dominance of traditional methods that focus on memorization and grammar, without being supported by contextual and communicative approaches. In response to these issues, STIT Internasional Muhammadiyah Batam initiated a community service program through an International Community Service (KKN) initiative aimed at implementing more active, communicative, and practice-based methods for teaching Arabic language skills. The International KKN program conducted by STIT Internasional Muhammadiyah Batam at Madrasah Darul Huffah, Johor, Malaysia, serves as a form of international community engagement with the objective of enhancing the Arabic language skills of the students. The program focuses on the development of four core Arabic language competencies: listening (istima’), speaking (kalam), reading (qira’ah), and writing (kitabah), using an active and contextual teaching approach. The methods employed in the teaching process include the communicative approach, talaqqi method, the use of audiovisual media, and practice-based learning. The results of the program showed an increase in students' motivation and participation in learning Arabic, along with the creation of a more interactive and enjoyable learning environment. Moreover, this activity also strengthened educational collaboration between Indonesia and Malaysia and provided international experience for the students as future educators and agents of change. This community service initiative is expected to serve as a model for the development of applicable Arabic teaching methods within pesantren or madrasah environments based on global community contexts.